Anaerobic Co-digestion of Rice Straw and Pig Manure Pretreated With a Cellulolytic Microflora: Methane Yield Evaluation and Kinetics Analysis - Zhong, Bin; An, Xuejiao; Shen, Fei; An, Weijuan; Zhang, Qinghua (Frontiers in Bioengineering and Biotechnology, 2021)
Agricultural wastes, such as rice straw (RS) and pig manure (PM), causes serious environmental pollution due to the non-existence of effective disposal methods. Urgent investigations are needed to explore how such wastes can be transformed into resources. In this study, we comprehensively assessed methane yield and kinetics of RS and PM anaerobic co-digestion, with or without pretreatment of a previously developed cellulolytic microflora, under conditions of their maximum organic loading rate. The anaerobic co-digestion results revealed that the cumulative methane production of RS and PM after bio-pretreatment was 342.35 mL (g-VS)-1, which is 45% higher than that of the control group (236.03 mL·(g-VS)-1). Moreover, the kinetic analysis showed the first-order kinetic, while the modified Gompertz models revealed higher fitting properties (R2 ≥ 0.966). After bio-pretreatment, the hydrolytic constant, maximum accumulative methane production, and maximum methane production rates of RS and PM reached 0.46 d-1, 350.79 mL·(g-VS)-1 and 45.36 mL·(g-VS)-1·d-1) respectively, which were 77%, 45.1%, and 84.3% higher than those without pretreatment. Also, we found that the lag phase and effective methane production time after bio-pretreatment decreased from 2.43 to 1.79 days and 10.7 to 8.92 days, respectively. Upon energy balance evaluation, we reported a net energy output of 544.84 kWh after bio-pretreatment. Findings from this present study demonstrated that bio-pretreatment of RS and PM mixtures with cellulolytic microflora could greatly enhance methane production and anaerobic digestion efficiency.